THE CONTESTATION OF RELIGIOUS AUTHORITY, SOCIAL MEDIA, AND LOCAL FIQH: AS’ADIYAH’S REJECTION OF USTADZ FIRANDA IN WAJO - Kuba, Imran anwar; HS, Muhammad Alwi; Asmullah, Asmullah; Hasanah, Nurul (Al-Qalam, 2025)
This study examines the contestation of religious authority between As’adiyah, representing local traditional ulama, and Ustadz Firanda, representing the transnational Salafi da'wah movement, focusing on the case of Firanda's rejection in Wajo Regency, South Sulawesi. The central argument of this research is that strong religious authority is not solely derived from online popularity but is instead grounded in social legitimacy, contextual wisdom, and an established scholarly reputation for maintaining harmony within a culturally diverse Muslim society. Using a qualitative approach with a case study method, this research draws upon a formal statement issued by the As’adiyah community. The findings reveal that the rejection of Firanda's da'wah was motivated not only by theological differences but also by efforts to preserve the continuity of local jurisprudence and the socio-cultural harmony of the Bugis community. Local religious authority, rooted in the legacy of the Shafi’i school and Bugis cultural values, demonstrates significant resilience against the expansion of purification-oriented transnational da'wah movements. This study underscores the importance of reactualizing local jurisprudence based on maqāṣid al-sharī‘ah to address the challenges posed by transnational da'wah, particularly in promoting the common good (maṣlaḥah) of the ummah and safeguarding local culture.